Role of acceptor strength on OFET properties of small molecular organic semiconducting materials with D-A-D architecture - Sasikumar, M.; Bharath, D.; Kumar, G. Siva; Chereddy, Narendra Reddy; Chithiravel, S.; Krishnamoorthy, K.; Shanigaram, Balaiah; Bhanuprakash, K.; Rao, V. Jayathirtha (Synthetic Metals, 2016)
Two organic semiconducting materials 2,5-didodecyl-3,6-bis(4-(11-dodecyl-11H-benzo[a]carbazol-8yl)phenyl)pyrrolo[3,4-c]pyrrole-1,4(2H,5H)-dione. (BCDPP) and 1,5-didodecyl-3,7-bis(4-(11-dodecyl-11H-benzo[a]carbazol-8-yl)phenyl)dipyrrolo[3,2-b:3',2'-e]pyrazine-2,6(1H,5H)-dione (BCPzDP) with D-A-D architecture have been designed, synthesized and well characterized. Both the materials have benzocarbazole donor end-capping units. While BCDPP contains well explored diketopyrrolopyrrole (DPP), BCPzDP possesses electron deficient dipyrrolopyrazinedione (PzDP) as acceptor moiety. The importance of the nature of acceptor moiety in tuning the charge transport properties of the synthesized materials is explored. Thermal, photo-physical and electrochemical properties of these materials are measured and solution processed OFETs are fabricated. OFETs with BCDPP show unipolar p-type semiconducting properties with hole mobility of 1.02 x 10(-4) cm(2) V-1 s(-1) and OFETs of BCPzDP exhibit ambipolar charge transport behaviour with optimal saturation hole and electron mobilities of 0.0054 and 0.0013 cm(2) V-1 s(-1), respectively. (C) 2016 Elsevier B.V. All rights reserved.